Process Machine Interactions Predicition and Manipulation of Interactions between Manufacturing Processes and Machine Tool Structures - Denkena, Berend; Hollmann, Ferdinand (Lecture Notes in Production Engineering, 2013)
This contributed volume collects the scientific results of the DFG Priority Program 1180 Prediction and Manipulation of Interactions between Structure and Process. The research program has been conducted during the years 2005 and 2012, whereas the primary goal was the analysis of the interactions between processes and structures in modern production facilities. This book presents the findings of the 20 interdisciplinary subprojects, focusing on different manufacturing processes such as high performance milling, tool grinding or metal forming. It contains experimental investigations as well as mathematical modeling of production processes and machine interactions. New experimental advancements and novel simulation approaches are also included.